2016
DOI: 10.5543/tkda.2015.28235
|View full text |Cite
|
Sign up to set email alerts
|

Arteriovenous fistula between descending aorta and left inferior pulmonary vein: closure with vascular plugs

Abstract: Echocardiography revealed systemic artery to pulmonary venous fistula, a rare vascular anomaly, in a 20-month-old girl, and multislice computed tomography angiography (CTA) was performed to rule out congenital heart disease. Normal bronchial connection and pulmonary vasculature were observed in the lung. The fistula drained through the left inferior pulmonary vein to the left atrium leading to a left-to-left shunt. Percutaneous intervention was performed in 2 stages using Amplatzer vascular plugs to close succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…A literature review showed 10 reported cases of cDAPVF. Four of the 10 cases were in adults and the rest in children and infants 1–9. Of the 10 reported cases, 6 were in male individuals and 4 were in female individuals.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A literature review showed 10 reported cases of cDAPVF. Four of the 10 cases were in adults and the rest in children and infants 1–9. Of the 10 reported cases, 6 were in male individuals and 4 were in female individuals.…”
mentioning
confidence: 99%
“…Four of the 10 cases were in adults and the rest in children and infants. [1][2][3][4][5][6][7][8][9] Of the 10 reported cases, 6 were in male individuals and 4 were in female individuals. Nearly all of the patients were treated with surgical ligation.…”
mentioning
confidence: 99%